The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11552-009-9219-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of the Transverse Carpal Ligament

Abstract: Transection of the transverse carpal ligament (TCL) for carpal tunnel syndrome is commonly performed, yet actual knowledge of TCL morphology is rudimentary and the anatomical terminology is inconsistently used. The purpose of this study was to perform a morphological analysis of the TCL, to redefine the anatomical terminology concerning the TCL and surrounding structures, and to evaluate any correlation between external, measurable hand dimensions, and TCL dimensions. A silicone casting technique and digitizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 7 publications
5
36
1
2
Order By: Relevance
“…Moreover, it has been shown that the flexor retinaculum progressively thickens from proximal to distal, and it is the thickest distally and ulnarly, although there is also some thickening proximally and radially (Pacek et al, 2010;Goitz et al, 2014). These anatomical features suggest that the pressure within the tunnel should be higher in its distal portion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the flexor retinaculum progressively thickens from proximal to distal, and it is the thickest distally and ulnarly, although there is also some thickening proximally and radially (Pacek et al, 2010;Goitz et al, 2014). These anatomical features suggest that the pressure within the tunnel should be higher in its distal portion.…”
Section: Discussionmentioning
confidence: 99%
“…Following informed consent, the patient underwent right carpal tunnel release. Intra-operatively, an hourglass-shaped compression at the proximal portion of the carpal tunnel was noted, as was a thickened transverse carpal ligament of 3-4 mm [15]. No gross abnormalities of the median nerve were noted.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 95%
“…Bilateral carpal tunnel releases (CTR) were performed without complications. Intra-operatively, the transverse carpal ligament measured approximately 3.0 mm at its thickest point bilaterally [15]. No abnormalities of the median nerve were appreciated.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 96%
“…Based on the classification of Amadio, Beris et al found that of 110 patients who had undergone open surgical carpal tunnel release, 11 had variations of the median nerve at the wrist [9]. The transverse carpal ligament anatomy is also varied, although no correlation between wrist circumference and actual dimensions of the transverse ligament was demonstrated [10]. pa cjen tów nie ty po wy prze bieg ner wu po środ ko we go na po zio mie nad garst ka [9].…”
Section: Introductionmentioning
confidence: 99%
“…pa cjen tów nie ty po wy prze bieg ner wu po środ ko we go na po zio mie nad garst ka [9]. Zró żni co wa na jest rów -nież ana to micz na bu do wa wię za dła po przecz ne go nad garst ka, lecz nie wy ka za no ko re la cji po mię dzy ob wo dem nad garst ka a rze czy wi sty mi wy mia ra mi wię za dła po przecz ne go [10].…”
Section: Introductionunclassified